PENGELOLAAN DESA WISATA KAMPUNG PATIN KOTO MESJID KABUPATEN KAMPAR - Shazlin Erina; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Kampar Regency is one of the regencies in Riau Province which has so many natural factors with tourism potential as well as various beautiful natural panoramas, customs and culture with various Hindu-Buddhist historical relics. One of them is the Tourism Village of Kampung Patin Koto Mesjid, Kampar Regency. The Tourism Village of Kampung Patin Koto Mesjid is a fostered village that has succeeded in making the name of Riau province proud on the national scene and was given an award directly by the Ministry of Tourism and Creative Economy in the Tourism Village Assistance event in 2020. The research method that will be used by researchers in this research is descriptive qualitative with the aim of describing a social phenomenon that is studied in more detail. The data obtained from this research are sourced from primary and secondary data as well as 3 key informants and 2 supporting informants. While the data collection techniques in this study used interviews, observation and documentation. This Tourism Village of Kampung Patin Koto Mesjid, Kampar Regency has a lot of potential such as the Mahligai Edge Pier, Puncak Kompe, Crow River and many more. The village management is divided into 4 functions, namely: Management, Organizing, Mobilizing and Supervising. A tourist village is a village that is the result of development based on the potential of the village and the addition of supporting facilities such as transportation and lodging. Apart from that, the natural factors and environmental conditions of the village are still beautiful and well maintained which are important factors for a tourism village. This Tourism Village Program does not change village activities in the slightest, even the activities of the village community become charms and interesting characteristics for the Tourism Village.Keywords : Tourism Village, Management, Kampar Regency